Revitalization of Traditional Jamu as a Support for Public Health at Malang Station: A Case Study of DPC ASPETRI Malang City Activities - Wibowo, Teguh Setiawan; Hidayati, Nur; Irawan, Richard Jimmy (Jurnal Pengabdian West Science, 2025)
Indonesian traditional herbal medicine (jamu) has a long history as a cultural heritage rich in health benefits. However, as time progresses, its existence has begun to be overshadowed by modern products. This article aims to explore the role of revitalizing traditional jamu as a form of community service that can support public health, particularly in anticipation of the homecoming tradition (mudik) during Eid al-Fitr. The activity carried out by DPC ASPETRI Kota Malang involved distributing kunyit asem jamu at Malang Station as an effort to raise awareness of the importance of traditional jamu in maintaining health during travel. This activity also aims to reintroduce jamu as a natural and safe herbal remedy. Through the distribution of kunyit asem jamu, it is hoped that the community will experience the direct benefits of traditional jamu while being educated about the importance of maintaining health with a more natural approach.